Pengembangan E-Modul Penggunaan Aplikasi Google Maps Berbasis Android pada Pembelajaran Tematik Tema 8 Subtema 4 - Lauzam Muruz; Maslikhah Maslikhah (MODELING: Jurnal Program Studi PGMI, 2022)
The need for third grade teachers at MI Nurul Islam and MI Darul Ulum is the development of e-modules using media or learning resources based on information and communication technology. There are no new innovations regarding Android-based teaching materials, media or learning resources in thematic learning of theme 8 sub-theme 4 for third grade. The purpose of this research is to develop an e-module using android-based google maps in thematic learning of theme 8 sub-theme 4 for third grade, in order to provide active learning and substantial experiences for students. This research is a development research with the ADDIE model, namely, analysis, design, development, implementation, and evaluation. Data analysis used a quantitative description approach through data collection using questionnaires, interviews and documentation techniques. The object of this research is an e-module using android-based google maps in thematic learning of theme 8 sub-theme 4, with product effectiveness as the benchmark variable. The need for an e-module using Android-based Google Maps comes from interviews with third grade teachers at MI Nurul Islam Semarang and MI Darul Ulum Semarang, who stated that there was no innovation in updating the E-module using Android-based Google Maps as active learning teaching materials. , so that it becomes the basis for research to make this research product. The form of the product in this study is an E-module using Android-based Google Maps as the program with the results of validation by a technology expert who gets a score of 95, and the value of a thematic material expert gets a score of 90. The effectiveness of this E-module can be seen from the average increase in field trials, which are divided into two stages. First limited trial with a score of 98.4. The second expanded trial got a score of 118.5. The conclusion of this research is that the e-module using Android-based Google Maps in thematic learning of theme 8 sub-theme 4 is needed in schools. The form of the development of this research is in the form of an e-module. The results of the e-module are effective for use in active learning.